2005
DOI: 10.1038/nsmb977
|View full text |Cite
|
Sign up to set email alerts
|

Model for growth hormone receptor activation based on subunit rotation within a receptor dimer

Abstract: Growth hormone is believed to activate the growth hormone receptor (GHR) by dimerizing two identical receptor subunits, leading to activation of JAK2 kinase associated with the cytoplasmic domain. However, we have reported previously that dimerization alone is insufficient to activate full-length GHR. By comparing the crystal structure of the liganded and unliganded human GHR extracellular domain, we show here that there is no substantial change in its conformation on ligand binding. However, the receptor can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
288
4
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(316 citation statements)
references
References 34 publications
17
288
4
7
Order By: Relevance
“…A potential clue here is offered by work from several other laboratories. First, it seems that growth hormone receptors, erythropoietin receptors and PRLRs are all dimerized prior to ligand binding (Brown et al, 2005;Lu et al, 2006;Qazi et al, 2006). This has long seemed more likely to the author since waiting for random collision of the second receptor with the complex between ligand and first receptor seemed inefficient.…”
Section: How Might a Different Signal Be Initiated?mentioning
confidence: 99%
See 1 more Smart Citation
“…A potential clue here is offered by work from several other laboratories. First, it seems that growth hormone receptors, erythropoietin receptors and PRLRs are all dimerized prior to ligand binding (Brown et al, 2005;Lu et al, 2006;Qazi et al, 2006). This has long seemed more likely to the author since waiting for random collision of the second receptor with the complex between ligand and first receptor seemed inefficient.…”
Section: How Might a Different Signal Be Initiated?mentioning
confidence: 99%
“…Instead, as previously illustrated (Walker, 2005) and as shown in figure 2, rotation of the receptor may well be the key. The potential for such a scenario is supported by some elegant work using the erythropoietin receptor (Seubert et al, 2003) and, more recently using the growth hormone receptor (Brown et al, 2005). Each study showed a one amino acid twist in the transmembrane helical region of the receptor to produce altered signaling.…”
Section: How Might a Different Signal Be Initiated?mentioning
confidence: 99%
“…This structure identified two asymmetric binding sites on hGH, called sites 1 and 2, which were proposed to trigger hormoneinduced sequential dimerization of the GH receptor, leading to activation (11). More recently, this model has been revisited based on the comparison of unliganded and liganded human GHR-ECD (12); it is now believed that GHR exists as an inactive dimer at the cell membrane, which is activated by hormoneinduced relative rotation of subunits within a dimeric receptor (12). In addition to the characterization of the structural changes occurring in GH and GHR upon their interaction, the GH⅐GHR 2 three-dimensional structures have also largely contributed to the development of GHR antagonists.…”
mentioning
confidence: 99%
“…The biochemical, structural, and dynamic properties of GH have been well characterized (11)(12)(13). The determination of the x-ray structure of human GH (hGH) bound to the dimerized extracellular domain (ECD) of its receptor (13) was a crucial step toward the understanding of GHR activation mechanism (14).…”
mentioning
confidence: 99%
“…Originally, this mutation was suggested to interfere with receptor homodimerization because it was found to abolish homodimerization of GHBPs. But later, Waters et al [23,24] showed that GHR is constitutively homodimerized at the cell membrane, which presumably involves contacts between transmembrane or juxtamembrane domains of each receptor chain. The activation process mediated by the ligand is assumed to involve a conformational change such as relative rotation of upper and lower domains of the receptor.…”
Section: Activation Failurementioning
confidence: 99%